Building Cultural Resilience and Societal Value: A Socio-Educational Analysis of Creative Entrepreneurship in the Indonesian Music Industry - Muchson, Mochamad; Hariyono, Hariyono (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aimed to explain the role of Rafi Record within Indonesia’s music industry and its contributions to economic, cultural, and educational development. Methodology: Using a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews, and documentation analysis. Rafi Record was deliberately chosen as the object of research located in Kediri City, East Java The research subjects include the founder (who also serves as managing director), musicians, vocal trainers, technical staff (arrangers, sound engineers, editors), and administrative employees involved in daily operations. Main Findings: The study reveals that Rafi Record has successfully transformed a music hobby into a multifaceted creative business encompassing production, entertainment, education, digital marketing, and intellectual property management. The transition from compact disc sales to digital distribution through YouTube and Instagram demonstrates adaptive entrepreneurship amid technological disruption. The findings highlight how micro-scale creative industries can achieve resilience and innovation by integrating cultural identity, digital literacy, and entrepreneurial management. Novelty/Originality of this study: This research contributes to the literature on creative economy and music entrepreneurship by emphasizing digital transformation and education-based business diversification as key drivers for sustainability in creative industries.